KEANEKARAGAMAN JENIS GASTROPODA DI SUNGAI JANGKOK KOTA MATARAM SEBAGAI DASAR PENYUSUNAN PETUNJUK PRAKTIKUM EKOLOGI - Robiyatul Ferisandi; Iwan Doddy Dharmawibawa; Safnowandi Safnowandi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2018)
Gastropoda included in the Mollusca phylum. Gastropoda are commonly found in watersheds. Jangkok River is a watershed that flows from the mountains of West Lombok Regency across Mataram City and interacts the most with human activities. This study aims to: 1) identify the type of Gastropoda found in the Jangkok River, Mataram City; and 2) developing research results on the diversity of Gastropod species in the Jangkok River in Mataram City as the basis for the Formulation of Ecology Practicum Guidelines. This type of research is exploratory descriptive research and development research. Descriptive research analyzes only to the level of description that is to analyze and present data systemically, so that it can be more easily understood and concluded, and exploratory research is a type of research that aims to find something new in the form of a grouping of symptoms, facts and certain diseases. While development research is an attempt to develop an effective product for use by schools and colleges, and not to test theory. Data collection techniques used for descriptive exploratory research are observation and documentation, while for development research are validation, legibility testing, and documentation. The data analysis technique was using species diversity index and percentage technique. The results showed that there were 51 Gastropod individuals consisting of 7 species that have been found including Potamopyrgus antipodarum, Mya arenaria, Ilyanasa aobsoleta, Pomacea canaliculata, Pomace ainsaluran, Poamarcobula amurensis, and Melanoides punctata. Species diversity at the upstream station has a very low diversity index with a value of 0, the middle station has a diversity index with a value of 0,91 indicating low diversity, and downstream stations have a diversity index with a value of 1,29 indicating moderate diversity. The average value of the validation test for practicum is 80,6%, and the readability test for students is 81%, with these results the practicum instructions that have been prepared are in the very valid category and do not need to be revised.